2022
DOI: 10.1098/rsif.2022.0024
|View full text |Cite
|
Sign up to set email alerts
|

Which lower limb joints compensate for destabilizing energy during walking in humans?

Abstract: Current approaches to investigating stabilizing responses during locomotion lack measures that both directly relate to perturbation demands and are shared across different levels of description (i.e. joints and legs). Here, we investigated whether mechanical energy could serve as a ‘common currency’ during treadmill walking with transient unilateral belt accelerations. We hypothesized that by delivering perturbations in either early or late stance, we could elicit net negative or positive work, respectively, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Differences in the simulation of trips, analyzed steps, and post-analysis methods make a direct comparison with existing literature difficult. In a belt acceleration study, the ankle joint was shown to compensate for the loss of balance using the work–energy approach ( 42 ). We also found a significant increase in the magnitude and rate of change of ankle plantarflexion net joint moment during the stepping response, which was observed over 41% of the stance phase of gait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the simulation of trips, analyzed steps, and post-analysis methods make a direct comparison with existing literature difficult. In a belt acceleration study, the ankle joint was shown to compensate for the loss of balance using the work–energy approach ( 42 ). We also found a significant increase in the magnitude and rate of change of ankle plantarflexion net joint moment during the stepping response, which was observed over 41% of the stance phase of gait.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a more ankle-dominant strategy as the initial mechanism to cope with the loss of balance due to sudden lowering of the platform ( 51 ), manual removal of the platform from under the foot ( 52 ), and unanticipated bump ( 53 ) has been proven in various studies. Another research used the work–energy approach and found that in response to a sudden treadmill acceleration (slip-like perturbation), the ankle joint best reflected the changes in overall leg work ( 42 ). The similarity of our findings regarding the importance of the ankle joint during the recovery step following a trip when compared to the results of the abovementioned studies supports the finding that the human body reacts to different perturbations in a similar way by utilizing an ankle-dominant strategy as its primary choice in balance recovery.…”
Section: Discussionmentioning
confidence: 99%